Artifacts in Histopatholohy – A Microscopic View - E.P. Sridevi Anjuga, N. Aravindha Babu2 , K.M.K.Masthan3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Histopathological examination is considered a gold standard procedure for reaching a final diagnosis ofvarious human body lesions. However, it is limited by a number of changes in normal morphologicaland cytological characteristics that occur as a result of presence of artifacts. The purpose of preparing abiological specimen for microscopic studies is to obtain sufficient and reliable diagnostic knowledge whichis a true representation of the specimen, whether it is for study or diagnosis. These objects may occur duringprocedures for surgical removal, fixation, tissue processing, embedding, and microtomy, and staining andmounting.They contribute to misinterpretation of the diagnosis of histopathology but often they bring thelimelight into the diagnosis. This article discusses the common artifacts which we commonly encounteredduring slide examination